ANALYSIS OF SUPPLIER SELECTION FOR PROCUREMENT OF GOODS IN KITCHEN AT LOR IN NEW KUTA HOTEL - Doni Eko Prasetyawan; I Gusti Putu Sutarma; I Ketut Astawa (Journal of Applied Sciences in Travel and Hospitality, 2018)
The process of procurement of goods and food materials obtained through the process or purchase activities. Purchasing or purchasing is a process of searching the source and ordering of goods or services to assist the production function in the production or service activities (Fausi, 1995: 1004). This research is titled "Analysis of Supplier Selection for Procurement of Goods In Kitchen At Lor In New Kuta Hotel". This study aims to find out how the procurement of goods in the kitchen and how to determine the supplier in the procurement of goods in the kitchen at Lor In New Kuta Hotel. The type of research used is descriptive qualitative research conducted through observation, documentation, and interviews, as well as direct observation of supplier selection by purchasing at Lor in New Kuta Hotel.